2016
DOI: 10.1515/msp-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Colossal dielectric constant of NaNbO3doped BaTiO3ceramics

Abstract: BaTiO 3 ceramics doped with 0.40 mol% NaNbO 3 were prepared using a traditional approach by sintering at temperature of 1250°C to 1290°C. The prepared ceramics was characterized by very good dielectric properties, such as high dielectric constant (1.5 × 10 5 ), low dielectric loss (0.1), and good dielectric temperature stability in the −40°C to 100°C range for the sample sintered below 1270°C. The dielectric characteristics obtained with XPS confirmed that Ti 4+ ions remain in the state without any change. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
6
0
4
Order By: Relevance
“…Moreover, giant permittivity values were reported in hexagonal barium titanate ( h -BaTiO 3 ) single crystals52, and the high permittivity values ~100,000 of the oxygen deficient materials were explained by the presence of interfacial boundaries consisting of crystal defects. In addition, it is reported that in NaNbO 3 -doped BaTiO 3 system53, colossal permittivity can be attributed to the high-energy electric state of Ba + (or Ba 2+ −e) by Ba 2+ obtaining an electron, which can create electron hopping conduction and increase conductivity of the ceramics. These charged defects like Ba + or Ba-vacancy are regarded to be responsible for the colossal permittivity5354.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, giant permittivity values were reported in hexagonal barium titanate ( h -BaTiO 3 ) single crystals52, and the high permittivity values ~100,000 of the oxygen deficient materials were explained by the presence of interfacial boundaries consisting of crystal defects. In addition, it is reported that in NaNbO 3 -doped BaTiO 3 system53, colossal permittivity can be attributed to the high-energy electric state of Ba + (or Ba 2+ −e) by Ba 2+ obtaining an electron, which can create electron hopping conduction and increase conductivity of the ceramics. These charged defects like Ba + or Ba-vacancy are regarded to be responsible for the colossal permittivity5354.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is reported that in NaNbO 3 -doped BaTiO 3 system53, colossal permittivity can be attributed to the high-energy electric state of Ba + (or Ba 2+ −e) by Ba 2+ obtaining an electron, which can create electron hopping conduction and increase conductivity of the ceramics. These charged defects like Ba + or Ba-vacancy are regarded to be responsible for the colossal permittivity5354. However, neither the reduction of Ti 4+ ions nor Ba 2+ was observed in our work.…”
Section: Resultsmentioning
confidence: 99%
“…A grande diferença de tamanhos de grão verificada na microestrutura dessas amostras pode explicar o aumento colossal no valor da constante dielétrica, em temperatura ambiente, observado neste trabalho. Tal comportamento é consistente com resultados recentes relatados em outros estudos (Cao et al, 2016;Dong et al, 2017).…”
Section: Regiãounclassified
“…Com tamanho de grão em torno de 1 µm, o material puro pode exibir constante dielétrica variando de 3.500 a 4.000 em temperatura ambiente (Arlt et al, 1985). Valores de constante dielétrica acima de 6.000 e, recentemente, valores colossais acima de magnitudes da ordem de 10 5 também já foram reportados para cerâmicas de BaTiO3 dopadas com elementos e óxidos metálicos (Valdez-Nava, 2009;Cao et al, 2016;Luoa et al, 2018). O BaTiO3 dopado parcialmente com cátions trivalentes e pentavalentes pode exibir característica semicondutora do tipo PTCR (Coeficiente de Temperatura Positiva da Resistividade), em torno da sua temperatura de Curie (120 °C) (Silva et al, 2012;Ertuğ, 2012), bastante utilizado na indústria eletroeletrônica como termistor (dispositivo de controle da resistividade em função da temperatura) (Ertuğ, 2012;Cho, 2006).…”
Section: Introductionunclassified
“…Barium strontium titanate Ba x Sr 1 − x TiO 3 (BST) is a solid solution family composed of barium titanate and strontium titanate with the Curie temperature covering a wide range from −250°C to 120°C. BaTiO 3 can transform upon temperature through the cubic paraelectric, ferroelectric tetragonal, orthorhombic and rhombohedral phase * E-mail: czhang1981@hotmail.com in descending order [5,6]. When strontium atoms are introduced into A site in a perovskite barium titanate matrix to replace barium atoms, the phase transition temperature from paraelectric to ferroelectric decreases and the phase transition behavior changes from sharp to diffuse, which makes the temperature stability of dielectric parameters of BST ceramics better than that of BT ceramics in the phase transition temperature range [7].…”
Section: Introductionmentioning
confidence: 99%